HIV-associated mucosal gene expression: region-specific alterations. (13th March 2015) - Voigt, Robin M.; Keshavarzian, Ali; Losurdo, John; Swanson, Garth; Siewe, Basile; Forsyth, Christopher B.; French, Audrey L.; Demarais, Patricia; Engen, Phillip; Raeisi, Shohreh; Mutlu, Ece; Landay, Alan L.
Abstract : Objective: Despite the use of HAART to control HIV, systemic immune activation and inflammation persists with the consequence of developing serious non-AIDS events. The mechanisms that contribute to persistent systemic immune activation have not been well defined. The intestine is the major source of "sterile" inflammation and plays a critical role in immune function; thus, we sought to determine whether intestinal gene expression was altered in virally controlled HIV-infected individuals. Design and methods: Gene expression was compared in biopsy samples collected from HIV-uninfected and HIV-infected individuals from the ileum, right colon (ascending colon), and left colon (sigmoid). Affymetrix gene arrays were performed on tissues and pathway analyses were conducted. Gene expression was correlated with systemic markers of intestinal barrier dysfunction and inflammation and intestinal microbiota composition. Results: Genes involved in cellular immune response, cytokine signaling, pathogen-influenced signaling, humoral immune response, apoptosis, intracellular and second messenger signaling, cancer, organismal growth and development, and proliferation and development were upregulated in the intestine of HIV-infected individuals with differences observed in the ileum, right, and left colon. Gene expression in the ileum primarily correlated with systemic markers of inflammation (e.g., IL7R, IL2, and TLR2 with serum TNF) whereas expression in the colon correlated with the microbiota community (e.g., IFNG, IL1B, and CD3G with Bacteroides). Conclusion: These data demonstrate persistent, proinflammatory changes in the intestinal mucosa of virally suppressed HIV-infected individuals. These changes in intestinal gene expression may be the consequence of or contribute to barrier dysfunction and intestinal dysbiosis observed in HIV. Abstract : Supplemental Digital Content is available in the text